Encounters with the invisible: revisiting spirit possession in the Himalayas - Lecomte-Tilouine, Marie; Sales, Anne de (Anthropology, religion, spiritualism, sociology of religion, 2024)
"This volume considers spirit possession in the Himalayas and the various ways in which invisible powers are made present. It does so by examining material representations of these powers through artefacts, animals, plants and natural substances, while also focusing on narratives of people's encounters with the invisible that may help them to reconfigure reality. Through these two approaches, the contributions examine new phenomena associated with the concepts of "possession" and "shamanism", which otherwise tend to lead research into well-worn furrows. The book addresses a range of themes, including the gods of the Western Himalayas, death and ritual dissolution among Hyolmo Buddhists in Nepal, gods and rivers as legal persons in India, and the problem of conversion disorder in Nepal. Rich in ethnography, this book will be indispensable for scholars and researchers of anthropology, religion, spiritualism, sociology of religion, Himalayan studies, sociology and South Asia"--